IMMU-21. DEVELOPMENT OF PET TRACERS FOR NON-INVASIVE IMAGING OF IMMUNOTHERAPY IN DIFFUSE INTRINSIC PONTINE GLIOMA. (23rd April 2019) - Nigam, Shubhanchi; McCarl, Lauren; Anderson, Carolyn; Panigrahy, Ashok; Pollack, Ian; Edwards, Barry; Kohanbash, Gary
Abstract: DIPG is an incurable brain tumor with median overall survival times of less than 10 months, with current treatment. Immunotherapy is an attractive approach for some DIPG patients based on promising clinical and preclinical studies. However, due to surgical inaccessibility, intratumoral heterogeneity, and lack of biomarkers, patient stratification and real-time monitoring of immunotherapy is challenging. Furthermore, radiologic enlargement of tumors, due to immune cell infiltration (pseudoprogression) may result in premature removal from effective clinical trials. Molecular imaging of immunologic markers may allow for non-invasive quantification of tumor antigen levels, activated T-cells within tumors, and differentiation of tumor progression from pseudoprogression. Based on our previous experience, receptor densities/cell, cell type specificity, and analysis of publicly available gene expression data we selected EphA2, CD69, and CD45, for development of antibodies radiolabeled with Zr-89 to quantify receptor levels by positron emission tomography (PET). EphA2, a tumor antigen, could be used to stratify patients for therapy. CD69, a marker on activated lymphocytes, could be used to quantify activated NK and T-cells within the tumor. Finally, quantification of CD45, a highly expressed marker on immune cells, could be used to measure immune infiltrates to distinguish tumor growth from pseudoprogression. We have developed an immunotherapy sensitive syngeneic orthotopic cell injection DIPG model (SB-DIPG-11), using tumor cells isolated from de novo tumors induced by sleeping beauty transposon-mediated integration of DIPG-relevant oncogenic genes. Intravenous injection of radiotracers into SB-DIPG-11 tumor-bearing mice demonstrated standard uptake values (SUVs) of 3.9, 2.5, and 2.2 for Zr-89-labeled anti-EphA2, anti-CD69, and anti-CD45, in the tumors, respectively. All SUVs were dramatically reduced by pre-blocking of targets with unlabeled antibody. Biodistribution analysis and flow cytometry validated the SUVs. Overall, our data suggest that immunoPET quantification of tumor antigen and immune cell markers may be promising for stratification and monitoring of DIPG patients for immunotherapy.